2014
DOI: 10.1016/j.surfcoat.2014.07.068
|View full text |Cite
|
Sign up to set email alerts
|

Tribological comparison of different C-based coatings in lubricated and unlubricated conditions

Abstract: The use of carbon-based coatings (hydrogenated and non-hydrogenated DLC, doped and alloyed-DLC) is of a wide interest due to its applications in mechanical components submitted to friction and wear including sliding parts in automotive engines. A tribological comparative analysis using a reciprocating (SRV) tester in lubricated and unlubricated conditions with a 4-stroke motor oil has been carried out on six currently relevant state-of-the-art coatings (namely WC/a-C, TiBC/a-C and TiC/a-C:H nanocomposites, Ti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
0
1
0
3
Order By: Relevance
“…The authors concluded that a high load-bearing capacity of the coatings is required to withstand such harsh tribological test conditions. This load-bearing capacity is related to hardness and mechanical properties (i.e., Young's modulus), with the volume fraction of (hard) crystalline and (softer, more ductile) amorphous phases, and the ability to form a graphitic-type transfer layer in the contact zone with low shear strength [97]. These conclusions point both towards the technological potential and the challenge of tailoring properties and performance of such carbon-based coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that a high load-bearing capacity of the coatings is required to withstand such harsh tribological test conditions. This load-bearing capacity is related to hardness and mechanical properties (i.e., Young's modulus), with the volume fraction of (hard) crystalline and (softer, more ductile) amorphous phases, and the ability to form a graphitic-type transfer layer in the contact zone with low shear strength [97]. These conclusions point both towards the technological potential and the challenge of tailoring properties and performance of such carbon-based coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Los ensayos pin on disk exhibieron coeficientes de fricción estables para las tres temperaturas de pretratamiento, indicando un desgaste abrasivo sin restos adheridos a los surcos. Los residuos actuaron como autolubricantes, provenientes de partículas de carbono con configuración grafítica (sp 2 ) desprendidas durante la prueba, como se señala en estudios previos [252][253]. Estos estudios indican una reducción significativa de la fricción para los recubrimientos DLC WC:C no lubricados en comparación con otros recubrimientos ensayados, con reducciones desde 0,22 hasta valores cercanos a 0,12 para los recubrimientos WC:C [252].…”
Section: Discusión De Resultadosunclassified
“…Los residuos actuaron como autolubricantes, provenientes de partículas de carbono con configuración grafítica (sp 2 ) desprendidas durante la prueba, como se señala en estudios previos [252][253]. Estos estudios indican una reducción significativa de la fricción para los recubrimientos DLC WC:C no lubricados en comparación con otros recubrimientos ensayados, con reducciones desde 0,22 hasta valores cercanos a 0,12 para los recubrimientos WC:C [252]. Los residuos autolubricantes pueden depositarse en los valles de la rugosidad superficial, facilitando su retención y reduciendo el área de contacto entre las superficies en movimiento.…”
Section: Discusión De Resultadosunclassified
See 1 more Smart Citation